Факторы изменения климата в южном Приаралье за 1961-2020 годы (SCIENCE and SOCIETY, 2023)
The article discusses climate changes in the Southern Aral Sea region that occurred in the second half of the twentieth and early twenty-first century. Since the 60s of the XX century, significant natural changes have been taking place in this region. The main attention is paid to the change in temperature and humidity in this region. An important role here is played by the increase in the area of the drained bottom of the Aral Sea. Aerosol particles carried out from the drained bottom significantly affect the air temperature. Special attention is paid to the convective removal of aerosol from the heated soil surface.